Outbreak of vancomycin-resistant enterococcus on a haematology ward: management and control. Issue 3 (May 2017) - García Martínez de Artola, Diego; Castro, Beatriz; Ramos, María José; Díaz Cuevas, Zaida; Lakhwani, Sunil; Lecuona, María
Vancomycin-resistant enterococci (VRE) infections and outbreaks are still infrequent in Spain. A six-month outbreak, which took place in a haematology ward, its control and management are described in this study. A total of 22 patients were colonised and two bloodstream infections occurred during this period. Even though there were two waves of new colonised patients, a multidisciplinary approach, quick interventions and enhanced infection control policies were required in order to control this outbreak.